GROUPING OF MUNICIPAL DISTRICTS OF THE ASTRAKHAN REGION OF SOCIO-ECONOMIC INDICATORS WITH APPLICATION OF FACTOR ANALYSIS - Marina V. Kolomeiko (Статистика и экономика, 2016)
In the article analyzed and identiﬁ ed the main factors affecting the level of poverty of the population in Astrakhan region made a multi-dimensional classiﬁ cation of municipal districts of the Astrakhan region on socio-economic indicators characterizing the poverty of the population on thebasis of the cluster analysis.